Penilaian Berbasis Kompetensi dalam Pendidikan: Kajian Literatur Tentang Kompetensi Pengetahuan, Sikap, dan Instrumen Penilaian - Dipalpa Rego; Remiswal Remiswal; Khadijah Khadijah (Indo Publishing, 2026)
Assessment is an essential component of the educational process because it provides information regarding students’ learning achievements and competency development. This study aims to analyze the fundamental concepts of educational assessment, learning competencies, knowledge and attitude assessment, assessment principles and standards, and assessment instruments. The research employed a qualitative descriptive approach using a literature review method. Data were collected from books, scientific journals, educational policy documents, and other relevant academic sources, and analyzed through content analysis techniques. The findings indicate that assessment serves not only as a tool for measuring learning outcomes but also as a basis for educational decision-making and continuous improvement of the learning process. Knowledge assessment focuses on cognitive achievement through various testing techniques, while attitude assessment emphasizes the evaluation of values, character, and behavior through observation and other non-test methods. Effective assessment should adhere to the principles of validity, reliability, objectivity, fairness, continuity, and practicality. Furthermore, the quality of assessment results is highly influenced by the appropriateness of the instruments used. Therefore, educators need a comprehensive understanding of assessment concepts and practices to implement meaningful, systematic, and competency-based assessment in education